2020
DOI: 10.4103/jehp.jehp_558_20
|View full text |Cite
|
Sign up to set email alerts
|

Ayurveda students' perception toward online learning during the COVID-19 pandemic

Abstract: INTRODUCTION: The recent pandemic of COVID-19 is very challenging for each and every sector like health, economic, technology, agriculture, industries, and education. In the field of education, a teaching institute or a university is suffering in regard to syllabus completion, clinical postings, and examinations which eventually ends up in huge academic loss. Thus, to minimize the academic loss and facilitate the students in distance education, online learning was the solution; in spite of various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 9 publications
5
25
0
1
Order By: Relevance
“…Online learning can better accommodate students’ diverse needs ( Zhu et al, 2020 ; Zhao et al, 2021a , b ), but it can also result in learners experiencing a sense of isolation ( Barak et al, 2016 ). Some surveys (e.g., Sawarkar et al, 2020 ; Velichová et al, 2020 ) during the pandemic have found that students do not agree that online learning is better than offline learning at school. In the online learning environment, students are subject to less supervision from teachers and peers, and there are fewer opportunities for interaction and feedback between teachers and students, which may lead to some more obvious negative learning consequences such as procrastination and inattention ( Cheng and Xie, 2021 ; Hong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Online learning can better accommodate students’ diverse needs ( Zhu et al, 2020 ; Zhao et al, 2021a , b ), but it can also result in learners experiencing a sense of isolation ( Barak et al, 2016 ). Some surveys (e.g., Sawarkar et al, 2020 ; Velichová et al, 2020 ) during the pandemic have found that students do not agree that online learning is better than offline learning at school. In the online learning environment, students are subject to less supervision from teachers and peers, and there are fewer opportunities for interaction and feedback between teachers and students, which may lead to some more obvious negative learning consequences such as procrastination and inattention ( Cheng and Xie, 2021 ; Hong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most reviewed studies compared online learning applications to traditional learning approaches (62 studies). Meanwhile, there are two studies that compared online learning with blended learning approaches – a combination of online and traditional learning [ 27 , 28 ]. The outcomes for all studies were categorized into four main categories: learning outcomes, student perceptions, student satisfaction, and student engagement.…”
Section: Resultsmentioning
confidence: 99%
“…Sometimes student finds online teaching to be mind-numbing and unengaging [10]. A number of obstacles and issues are raised by students concerning OA [11][12][13]. Few of the related studies were reported [14][15].…”
Section: Discussionmentioning
confidence: 99%